2004
DOI: 10.1111/j.1442-200x.2004.01955.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy of enalapril and losartan attenuates histologic progression in immunoglobulin A nephropathy

Abstract: Although only a small number of patients were examined, these clinical findings suggest that a combined therapy of enalapril and losartan may attenuate histologic progression in at least a proportion of patients with severe proteinuric IgA nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…It is reported that urinary angiotensinogen levels are higher in IgAN patients compared to control subjects [14,15]. Furthermore, recent studies showed that treatment with an ACE inhibitor and/or an Ang II type 1 (AT1) receptor blocker (ARB) provides antiproteinuric and renoprotective effects in normotensive pediatric patients with IgAN [16,17]. These results suggest that intrarenal RAS activation plays a critical role in the progression of IgAN.…”
Section: Introductionmentioning
confidence: 62%
“…It is reported that urinary angiotensinogen levels are higher in IgAN patients compared to control subjects [14,15]. Furthermore, recent studies showed that treatment with an ACE inhibitor and/or an Ang II type 1 (AT1) receptor blocker (ARB) provides antiproteinuric and renoprotective effects in normotensive pediatric patients with IgAN [16,17]. These results suggest that intrarenal RAS activation plays a critical role in the progression of IgAN.…”
Section: Introductionmentioning
confidence: 62%
“…With the exception of Praga et al [61], these were case studies involving adult patients. There have been few studies in children with IgA nephropathy, except Tanaka et al [63] and Bhattacharjee and Filler [64], who demonstrated the combination ACE inhibitor and losartan to ameliorate progression. But these were also case series and neither was a double-blinded, randomized, controlled trial.…”
Section: Clinical Studies In Prevention Of Progression In Iga Nephropmentioning
confidence: 99%
“…To our knowledge, only two published studies describe the use of combination therapy in children, both in children with IgA nephropathy [5,6]. In neither of the studies were the patients treated only with angiotensin blockade; most received concomitant immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 96%
“…This combination has been shown to reduce proteinuria and blood pressure (BP) more effectively than either drug alone [3], and in a single randomized controlled study, it was also associated with better renal survival [4]. While there are some case studies in children that have reported the safety and efficacy of combination angiotensin blockade, none has used angiotensin blockade as the sole therapy for treatment [5,6].…”
Section: Introductionmentioning
confidence: 99%